Narratives of Translation and Belonging in Multilingual Performance: The Case Study of 20/20 - Komporaly, Jozefina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This article investigates ways in which theatre and performance have the potential to revisit and re-interpret ideological narratives. Drawing on the politics of transnational performance-making processes, it examines how multilingual theatre productions can contribute to the production of subjective and collective identities, and help articulate ideas and perceptions of belonging. With reference to 20/20 – a piece of documentary-style theatre about a major inter-ethnic conflict that took place in 1990 in a bilingual city in Romania – this case study maps out arguments for utilizing multilingualism on stage, and engages with the ethics of representation in the process of multilingual transfer. Billed as ‘multi-ethnic and multilingual’, the production embraces an agenda that goes beyond the examination of an isolated local conflict and makes the point that both theatre-making and theatre-going are experiences that strongly interact with narratives of cultural identity and hybridization. Thus, the representation of belonging or not belonging is tied in with questions of agency, and the right of individuals to affirm and indeed interrogate their hereditary links to a community.